A new micropterous winter species of Leuctra (Plecoptera: Leuctridae) and little known endemic stoneflies from the Greater Caucasus - Teslenko, Valentina A.; Palatov, Dmitry M. (Zootaxa, 2019)
A new micropterous winter emerging stonefly species, Leuctra abkhaziae sp. n. from Abkhazia and western Georgia in the Greater Caucasus is described and illustrated. Descriptions and illustrations are also provided for larvae of the little-known Caucasian endemic species Leuctra simplex and perlodid Bulgaroperla mirabilis caucasica.